2013
DOI: 10.1039/c2dt32432f
|View full text |Cite
|
Sign up to set email alerts
|

Organosulphur and related ligands in Suzuki–Miyaura C–C coupling

Abstract: Suzuki-Miyaura C-C cross coupling (SMC), an important synthetic strategy for many organic molecules, has several advantages such as mild reaction conditions, high tolerance toward various functional groups and ease in isolation of the product. Palladium(II) ligated with phosphines (particularly bulky and electron-rich) and N-heterocyclic carbenes (NHCs) has been found to be efficient in the catalysis of SMC. The drawback with many of these catalysts is their air/moisture sensitivity. Since 2000, palladium(II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
115
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 167 publications
(343 reference statements)
0
115
0
Order By: Relevance
“…Palladacycles and Pd II complexes ( 1–5 ) of these ligands have been prepared and explored for Suzuki–Miyaura coupling reactions. The in situ formation of Pd‐containing NPs has been reported in Suzuki–Miyaura coupling reactions catalyzed with palladacycles9b of the organosulfur ligand as well as Pd complexes of sulfated Schiff bases 12c …”
Section: Introductionmentioning
confidence: 99%
“…Palladacycles and Pd II complexes ( 1–5 ) of these ligands have been prepared and explored for Suzuki–Miyaura coupling reactions. The in situ formation of Pd‐containing NPs has been reported in Suzuki–Miyaura coupling reactions catalyzed with palladacycles9b of the organosulfur ligand as well as Pd complexes of sulfated Schiff bases 12c …”
Section: Introductionmentioning
confidence: 99%
“…The calculated geometrical data clearly indicated that the change in the squareplanar core was not considerable when going from the anti (27) to the syn (29) conformer; except the Pd-N2 bond, which was slightly elongated to 0.014Å.…”
mentioning
confidence: 83%
“…Recently, the promise of metal complexes of organo 1,2,3-triazole-based ligands has been demonstrated in the catalysis of some chemical transformations, 27,28 such as hydroformylation and intramolecular hydroamination.…”
mentioning
confidence: 99%
“…The reaction has long been the subject of vast research in transition-metal catalysis. Various transition metal complexes [71,72,73,74,75,76,77,78,79] (e.g., Ni, Au, Co, Cu, etc., as such or combined in pairs as heterobimetallic catalysts), or nonconventional Pd(II)-complexes with intricate organic ligands containing S or Se have been intensively explored [80,81]. Efficient transition metal-free catalysts have also been reported for Suzuki–Miyaura cross-coupling reactions [82].…”
Section: Introductionmentioning
confidence: 99%